Violence against women in colombian criminal legislation (2018)
This article explains and analyzes some criminal prohibitions that, according to the author, penalize some types of gender violence, which are enshrined in the Convention of Belem Do Para and which is introduced by the Law 1257 of 2008 to the Colombian le